Nilai Moral Tari Kembang Lambang Sari bagi Masyarakat Betawi menurut Perspektif Hans Georg Gadamer - Riandari, Wiwit; Nursilah; Tuteng Suwandi (Program Studi Pendidikan Tari FBS UNJ, 2023)
Dance which is seen as a text, regardless of its type and form, will certainly contain a value. Moral values ​​are one that is important to know. Moral values ​​will be a guideline for determining good and wrong in society. Exploring the moral values ​​in Kembang Lambang Sari Dance can be done in various ways. One way is to dissect its structure through discourse analysis. Discourse analysis is carried out from the smallest structural components, namely motives, phrases, sentences and clusters. The relationship between the components will result in an interpretation of the dance movement. Analysis of Kembang Lambang Sari dance structure is then combined with an analysis of the dance character from the concept put forward by La Meri, the concept air design which describes the impression of movement. The results of this dance suture analysis will ultimately be studied through the perspective of Hans Georg Gadamer's hermeneutics, namely Fusion of Horizon, to obtain the moral values ​​contained in the dance. This study aims to dissect the Kembang Lambang Sari Dance structure so that the moral values ​​contained in the Kembang Lambang Sari Dance can be interpreted clearly in accordance with the values ​​to be conveyed by the choreographer.